“A sparkling example of what aggressiveness, imagination, and skill can accomplish”: The Rise of Dubreuil Brothers Limited, 1948-1973 - Commito, Michael (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
This article argues that the brutal aftermath of the catastrophic Mississagi forest fire in 1948 enabled Dubreuil Brothers Limited (DBL), formerly of Quebec, to grow and develop while salvaging timber for the Crown. The Ontario government, so concerned with getting the project concluded, essentially tolerated sub-par performances from contractors such as DBL for the sake of expediency. The salvage shaped DBL’s formative years, but its success after 1952 was largely due to its drive and resolve. Part environmental history and part business history, the rise of Dubreuil Brothers Limited tells the distinctive story of a company that defied the stereotypical views of French-Canadian business. It may have been forged by fire but it remained viable through entrepreneurial spirit and ingenuity.